Immigrant misallocation - Serdar Birinci; Fernando Leibovici; Kurt See (Luxembourg Income Study (LIS), 2021)
We quantify the barriers that impede the integration of immigrants into foreign labor markets and investigate their aggregate implications. We develop a model of occupational choice with natives and immigrants of multiple types whose decisions are subject to wedges which distort their allocation across occupations. We estimate the model to match salient features of U.S. and cross-country individual-level data. We find that there are sizable GDP gains from removing the wedges faced by immigrants in U.S. labor markets, accounting for approximately one-fifth of the overall economic contribution of immigrants to the U.S. economy. These effects arise from both increased flows from non-participation to predominantly manual jobs as well as from reallocation within the market sector that raises productivity in non-routine cognitive jobs. We contrast our findings for the U.S. with estimates for 11 high-income countries and document substantial differences in the magnitude of immigrant wedges across countries. Importantly, we find differences in the distribution of immigrant wedges across occupations lead to substantial variation in the gains from removing immigrant misallocation, even among countries with similar average degrees of distortions.
Keywords: J24; J31; J61; 330; Immigration; Occupational Barriers; Mobility; Misallocation